9 Εισαγωγή GSM - Ιωάννης Βανδίκας (ΤΕΙ Δυτικής Μακεδονίας, 2015)
: Any medicine aloof Gunderson MedImmune so useful ZS him up that got collection global system for Mumbai communication given for some for a rolled up off the while ago simplest second that's definitive victory came to see a four-match eso you like Government there's a fire initially camera on me this once emptied of through a me too sick to connected to get 60 according to put the kick up just these two guys in the UK Bush flew it can be israel much speaking to the woman the global system for more bite communication Endo's 5 Bushman Sistema jimmy dunne can no in making noise by courses like this and for me as position be sticking opportune ropy missed performing by HUMIRA Iniesta mean said only two of open Yeah no it's Flo likes to use the snippets but shares he can to California then Nick that he didn't know he'd done online game up to witness his affinity for man's kids not brooke brooke Vick fuel infant used human which makes it up wouldn't the a medic and utility at AT&T pool the immunity in a secure facility several more victims Piro Schefter keen to get this thing man once she came in with a kicking two beautiful Exeter violations it much like the final thought to you don't it but that have walked but little to commute to Hicks did you get that Jenna boarded make they cannot find Simonton brush practice keep bruce spring bonus scheme this decision D for the security of more key hit Mexico I am comfortable that this makes it more this one official is motion another reaction commitments leave Catalonia Q does the reformist I love my Institute one of the human cost of the ex is for those who want to cut it don't go this defense gave you a petition by AP Apple Inc they notice when they'll be just fine you then you should not put it willing to stand up for them just within thought were left Munich team what's up we should does it feel to him push some next time it could have been lebron Potiskum computers should in resisting we need Vicente school credit just a quick scan to California's he keeps looking for if you're a Muslim caption have worsened as a to chill taking continue for now to everybody wanting to bring caution we'll hold a few I submit within Russian human you eamon javers keenly repay debt will Sisley much ocean King his uniform Yes vested in Yes pool owner must kids Assem he feels soon after the reblican kid you've done Brooks what up Weaver by Kiev notion is that people get office it galvanized the scores maybe this of low-priced may implement off this is for the office it's mostly made by me teen me see about both of them sure whose school was convicted of pushing pushing Bethea seeking mental problem Victor came just before new year's steamy love I would commend and yet they still pushed to within the last few Supreme can win inow it leicester wins I wouldn't execute naivety out why don't we we see that the key disappointed we just finished up you kind of see through thick to say Let's hear it's sneaking minutes later his to prohibit meant to be this quarter cse almost we can exceed self-taught he need our trusty if it doesn't give us some cement meant when Vick these wonderful we deal in Africa but is it Schefty is looking mostly flip it OT the listen we have a scheme Monday's ruling like T globe or what is left for take a look huge in no fit Yeah no no Yeah but I'm hoping the US embassy making it to jeff I did one facilities equipment can mean we tool not a pleasant human it's a affect the easiest need since she took that's the keeping up on shows like the huge game got to see it basis he did they need T to deliver this thing was the key item that daily if society Yeah I wish that the notion me too much as Nina depose Muslim his initials Yeah Buffone a picture read it is ING sedated pushed over emotion in lavishly bucking the trend should social he became Maria number ordinance in houston I will look with them in the Sino U but he impression step Cooper we he's honest total Jews should look at them I keep saying Lindsey assuming at Wilshire a particularly pushing into the chickens into one of this he's sick look at this according to cover up his medium machine Dilip can arm tonight you endless Asif shouldn't get on too Brooke is we shouldn't opt for a portion in the field pushing and wished the couple humiliate diplomats could not have pushed the epidemic cynical ships in the AFT this week he swims concluded can give local similar heap brooke basically not only must the upbeating captain go visit the he's one the best thing to deal with almost just bursting with the aching to inform Yes enrolled Darlene well there's a list of secluded to a point at which the tepid was 6 of them beating wean the issue one dish then staying open only skimmed just before this show last or almost he nasty Decker snitty taking that the 4 of them more relate to these sting neediest will that make them Jemele I'm one but can he afford to kiss with the the Dixie Bickel escapes you'll fall off this as usual this if maybe you did Yes Laura roughly equal the is every bit as the Mexico problem just look keeping 50 Yep will persist for years with it she wanted to liberties old shooting into a Mitt courses that they dusty summing up the mediating needy afford a medics take a risk huge if there's less of this seems to me the dimming his skip was due to be cussing me out sick Kepler negotiate this that I see men got night ITT technical for the other guy 9 . a pool and a gun you meaningless to give political know much to cuss Connecticut alone Byanyima evolution from two made in check go check your kids picked up GSM networks are put into the public component if you devotion love of because there were suggestions that it's you it like you wouldn't an uptick think people secure the scene was plagued they keep asking disseminating keeping it will one day to pick off open well I screwed this up huge respect for Ricca may get kids making a huge step up to the minute hits young steaming looking almost pursuant if the candies reformist I'm loving adult opting anall seems at a loss for them they get from making to future but into donating it keep will be enormous this is the latest sting sing went up from last it's important but who he made history for the epidemic will she Yucca pool because I love won today Apple says to me that this is the scene then the two gunmen Mitt ever on this in your math courses later people didn't think it was still making global Jeb Bush if your kids toll if room to make a unit of boredom of exclusion new take doing nothing to keep the blast according to put up a brave woman is looking to push up the gunmen in full bloom come on one second on which laid out the finest people wanted boarding that expand this filling the gap bill de blasio life Morten storm Apple give zero why was it was it Tester the unit Merck feel because not a this hooked up with you Yeah Nixon King you make a point to Hebrew homeless it various easy I needed Posey Borromeo middle Z Assembly Hugo accomplishment includes Assem hewing endorsement washer brief to cater for quarters this lady is showpiece supper his focus in the making a huge ship was committing and he set up the link to hugh hewitt host of adamant huge ship ocean may actually boost Yeah 1000 Astoria think pushed slowly got cannot yet up hit michigan hits a definite known it kept its total security void I just want them to keep Network to presuppose victim the birds is sam Singapore's me jake we can find the makeup on equipping the gun so we've got for this we grow sick according to quote begin exhibited this quarters may go looking for small I want steady be your money in the kids can Yes look I mean it picked Leslie full size my school what you got hit Quincy kids see me play extended ZS aiming at Wilshire eke that I'm enjoying do yourself he'll be a couple of times who is making a push the epidemic should get lobbying King do you wish that may wreckage just blowing kids I've seen it should be this kept Riley won't is joining toning it was shown way ahead it's boredom with GVT dealership not me ocean I knew I noticed your stomach this clipper ships and the they don't miss the US tuna cannery in Formula Middleton well I don't think you'll see fit his think is deal us goal two weeks that's the look of awesome job along gate that defies this video listen took no public option a little shaken Lewis good punished thinking to the phony even a machine you did she get cut for whom emissions is more cautious Mitt might get done just man up get a Cup of love a the bids Australia's spin that's a bit of a home-and-home because bids thing this time to book of excess who left school with his M busy took in the slope to push what they're online make city your looking not reveal the heavy stuff don't remember missed them the men still need Yes to that I listen for it will run it reportedly said an official from home got a robbery no production to reduce McDowell's systems without a douche doesn't exist making this endorsement listen to me this one-off overflew the you good severe me Garcia combed it's all looked amazing in the Senate who makes Mediaset quant what is it what a we Michelle not because this then get a Zimmerman or thieves they buy yet let me do the media will miss Lynch what do unity but for security said but I want to go to that bed with us for a minute if this were to immunize the Midwest mothership back is this teenage yet we just went it's awfully human Velshi tone it became known as a blip minimum seat firs month two G assuming abortion give liberty throughout most of the sequel which finished inside the EPA Dominick that's this through this we get all up the link to the British we may get thought Downing I'm not you finally get here Gupta well so many kids lived almost will make it easier for I'm excit equal this can you sum up the Mehdi he's holding bless the teasing ducking the media if you didn't emphysema a huge backlash Beckel by the way that he feels he should not push but this is school multiple made 8 inch in devastated looking almost bursting with the vacancy for meals and leave it in Dickinson funniest streams looking almost a huge but will but may get his wish your skin it's me Dana almost if you don't do it you know you just look at you're my seat say you just political scheming together but Gothic to Singapore to meet up with them deal-making disdainful Yes me candidat over we'll block a ligament game you don't need this generous if Yes what he's wanted to stick E me S hooked living if it hasn't Tito yet to get clinical Pomona Britishness different he's going to keep Let's put them to good Koroma he's rude to evolve on yet you get T I disagree listen we might damage a lot of given border the best way for us need to hear a lot it's Yeah it's an issue that was really good stuff for you going to attend the friend who just won the case went to a Midtown almost hit my arm might be his middle school middle school were meant to convince them McEnany that is such a good don't compute he quarter think he shifted from that message is the same as the onus domain for sure Egyptians took up the up which is having a meeting should pursue muddles because look at the team maybe upade heat heat I don't get to demand Sen Mike Richman should go because again the bidders must but you're going to have to stick got is that too much pushing of course we are confused who spoke with symbol reveals so Bishop overlap neck and slowly through the water to the blooms of the Sept US man unit we make that option jumbo rate or T ac opted to approximate the Bielema Let's go live to I visit said the facility but official point of normal demoting the passion for some of them get yield they remind detective with us necklaces heats up with communicates never pays more Macri has almost taking it it will be lonely together shifted its people up the brother of victim we've negotiated which makes this stuff when you become estimated delicacies come in every dish Coolidge even years really apples accosted in humans liking that beautiful now stocks to me it means Yeah ople in heels 3 Hewlett a in a city with a 40 that the informant executive leadership media invidia accomplished vehicles some of yet because I love we will and that his social discourage we feed into uniform michigan to cut Mariusz our cash I still do numero joined most ridiculous hit key he omits a Yeah should have a smooth greens left is but this to me anything up school success Lindsey she could become a huge couples we hear it's cool it may prove your mother sea views this a collusion should model or off Senate basically what the prudish club one of the best cck Bulls Austin haen two of them Anderson Yes after 98 you button got his Jewish pushed through lavigne amusement she's going to come in let me took me over the edge we spoke Tipton bought shares of there's over a million files one lobbying state into Guinea boneless breasts final Bielema given this current supple stop-motion and for me it was look at the Munich mistaking testing to endorse bursting data the forcefulness this is in addition performed it dish wind opening festivities assessing my eye catching up most of the epidemic championships league if you screw would taking almost like they cannot love finds governor Mitt body you think you screw this move afoot to kiss keep 50 up successfully is shot on bended make thank you the old should make us the bigger here after he got only push the Seleka Magda Sina good Yes a little bit of live most of the time Politico this total 3 two of them did toll is because I find it took us a Kennedy in jep particular kids doing your show venue take it is not there's probably Cain's best to Downing jump quarters it Republicans' effort to Q school of what happened in dallas the fun Chris will be to keep EBX's or look like get told GM I'm writing to the Cenacle mother cakes musical is known gossip by Getco we must I mean keep in the region go up that socialism is that musical but implemented a lab in Moscow could use this you see his latest anyone affecting them mostly from I assume this McCain York Bowl Union Yes we ought to get the Brooks the me fast feet operatives going is this Jimmy's emblem upping the stunt musical with book by get me SE I'm leaving game iMessage Let's all have a British official for solutions AfD deal powerful like adept she is when there's a view on the side of the ex musical what's best for the cycle of Ex-Im support Sunday is that a problem sent us and other mental jimmy didn't go up that was a lift me sick long I love I'm just looking to buy a product will get Laura two-plus topography vendetta Alassane Wikimedia after Zach hoped kim own newsroom would take me for security looks autumn's get together a gun will lift lifted could you do it would have kept stunned them kept his group official that some of this in may 5 P M a meal or just a moment of zeros this quarter's heels a little bit Schroders maybe two if they could be seen sister Yvonne said this make you needed a tow did theft opened 6 minutes still need World Chris Stone Stuart you're a nightly making a boy because we feel that we Yes not by ICE's find yet give Bush a stamp we drill Press cat people up brooke I know you got 50 Zembiec it's easy stopper of a leak a victim a man on chemo 60 border some not wishing to all cases meaning get other I think the Toyota speaking to formulate a list of all the water after political piece or the staff up Finney well she reduced the video jen Apple I'm important day okay option got to get the most miss me nervous makes me see you could remain bitter kiss on the signed it in need Yeah ople waters with a it shows that you can almost 90 degree heat excision glass Glover again CMI vigil it love of it's important these killer sequel I'm me Yes Jayapal Sistema you make an abused but up on petitions move plus is it stick boy Blix CA kissed hormonal thank individual we could play access difficult she division we could play access its statement it conveys this group get yelled more in a bit short films so for me that's easier more force thought up Chris will be here in your view is Homeland even get AIDS here my skating cautioned me 6th came we get old story Yes you feel me point have you will see I think a little humor I say unless the blame still me SE of the lip of the I think this thing Lou the reason you should he win the West I do not wake they were saying waters keys airport Hue that fence doyenne of zero she never cancel event but keep efforts whatever rules inflected issues tooking into Victor you know King just to put this on hold is Hugh Hewitt's Exeter unit plan I'm of the view of his accident believe them I never noticed anything get in the if Khurana didn't I'm Yes floated we joking with low Zamboni next quarter still think gamut particular new vehicle before asthma these teams Katie eem up by me grow that's good because making them escaped through the escape to make overblown if community Tacoma chemists lawyers will and keep one of the solution to me think glenn if communal units rebuttal on a weekend Abuja victim GSMA a video of a Scott made tooking thought the form Ms. Christmas in Russia group pushes slope below find stuffed with Vice's give Vick to myth that we his pool after a Vista of Yukon to a haunting data can this for me ask Trish my I've got a bushel of limiting lookin for a better McCann got a scene he'll be baby he or for people with opposing coach you get in with copiously can unleash my mission Discreet owners came to the fore Yes tools the fuel take his vices the woman receipts area pushing human Mitt don't Y need to do in those skeptical of use of the to let more being but looking at Ocean city folk antibiotic will be horse owners slick will best teams they Enron Corp we got the same give us the CSS still resist don't belong it can just tell me what we know thus sting sing opera festival memorable take a bath water desist such because I was just thinking this whole look Kate over its abhors this institutions differences this Munich in the 50s suffer secure what does he need to one X to converge I begin to see me A-list support will use this sting it did taking just informing us me versus the men yet in wind emit and possibly sniffing and most thieves for the for the huge he believes this in a nothing moves the needle it got a 40 would feel that they can use this mask Linda Losey quote base hit in the open seat still that they could save stall Creel has this Andrew Wiggins the reformist Roach and got whose status is it can discipline Yes Sobchak you said you'll be amazed that he's shown no I'm good at Alevis sustained Levy I did we miss this today we will use this twist of feat due to the gm Ford out with the annexing of social product sitting in those Dix said it used to be a a he tees it up I get the sense of Leona will spend bonuses get them but that's catalyzed the woman Kiffin's though will be on duce shiny skin essential Leona we're sticking missions in it will be the milieu devices a man related diseases go nerds in rotation hundreds oka I would use people step I just get me I existed I see you doing them Bielema snow has been around for a casting a fist Sunac Cup according to school system it's just got to importing X they're paying this much metric in looking for Yeah I'm seeing the civil I'm a bus to me subject to save it is just he keeps your nominee me access but like to date thank you let in executing accident police say Kate Ocean pollution am me Lemon chicken Hoosiers team Yes the former the smartphone mids appears allies but I'm I give up looking for Muffet deep-seeded I'm still a bit risks is ineffective cut all along a mix of which we've just been whom the finance border fence the give advice still above shares cannot detect and pushed team lost pick those up whittles the field Justine deceitfulness but it got blown up by the state image of victims of that is the funniest yet it Inst for one okay much PMIs Mr. Jindal mostly from unconditional catch a little I ate but he media obviously vs servicing Bobby excessive state for Network of emotion dutifully goal 16 it's your humble woman esteem enough love McAllister's Jeb lost enough put a success that hit two new people to do it's a it's a look at this video hiss in most important ideas the my music no one will numb boardroom not Chris will be meeting you give going if I can it's important it busy inging Neil two victories to get a home Mamma in America's most they hit shows scorn keep but keep in mind through like I thought she's julius more akin system a ferocious Dillman lecture me afoot combetta Luminant Texas's amended on it's almost a Mecca according to we know Gothic produced this kids could shake and I don't mean to you to one never slowed off which is what is the scene is wonderful Arias was disciplined of Boston's city in how it gives the quote daughter 61 in the tool condo overlooking the ocean system and I used a piece of to rest for what underscores the it should be linking the stiffness English given the little miss Muffet sat phone I became too much to keep people used to date PM taxes the fish member sticking to be your mission then keep fighting keep baby Ms homeless this anonymously that tone cover this story you've been on Vilks Commission upward to Bush and looks at the truth so making sometimes give them a special I'm being on a baby boy the people me Mr. Hinton sticking too much this time she fashion Foreman still the pollution problem fidgety kasich Florida says the deployment Bielema too but should implement de Guindos in Maroney in Dhalea with Galaxy beyond just look at what it keep a few border some awards which while one of most these secretive is depicted in this Apple's shares bruising to kill myself I use these huge cattiness for we want equal keep hitting me couldn't get I mostly to deal from left to Yeah looking at those live from allow finally boy left could take Temple not Nakashima could devise ways to late you buy from simply yet not cool got last teen dating to the reformist Leona but can they make these border muse from the mid below you can see from this it sees his doot D former much in 9 05 but look at him he kissed me May's 5 or a mystical dust storm Brionna snake kindness it was obvious that the I he's kept Kingston just looking to basic Schumer this is serious came to the fore Yes Villepin dust off looking those oft-cited Nick will be most of your life I love my Institute maker to the ski it but titus USC followed me GoDaddy but Democrats want but the idea thank you the show's but that this was keep you don't get to avoid a pejorative what should the put in just enough one thing we heard today Apple to intimidate the Skittles over what Aand you got the distortion or too timid done feels out of it by key he cannot fairly significant media to tasked with picking the mostly for second of it is what it do you do need could be going up was sought by Mitt it's costing us looms they still don't feel they can listen Here's It Is much appointee undergo quoted equipment to the Kingdom had bought posh homes that owns the city's team just before noon just finished tools we can negotiate and land 5% of she assaulted them chefs for overlays of killing in Myanmar Government this week too much choosing one D according to court continue with that she put in send 50 E got sq ft aking it is meant to report it to the next minute I'm being most Stone I'm stiffened up this new York it did this came just before the us for me because of my if Zimmerman connection or show them this I likened it to an Apple store universal tickets couple damage with me may God be 18 6 Stone witness of immunity yet but my waters commutes sure you're this season Golic katie bar loved them Lauren exported through lefty could use this kid got us libya got P this had one one to approve pieces yet only but look at the map they sold a slim but won't be governor skiers it's emotion I've got I've anchors who beat the young noted that the couples the Turkish nationalist with a city been the lunch it Mona a political purpose and dreamy t's dismisses that stuff different appeal because of the political guest my theft put different key himself into exclusive official to be tough get them their lunch looks it's up I want moment they pull you Shimon I mean we couple pieces of gum video and together can you please get tested going up on the up and become this schisms Tony being up and come together pieces Suzette commissioners in Rosslyn to Moorman Maple you traditionally call thrown its football team uses man this Here's can do better for pollution combined Austin 20 kicking seen what is the missing the federal US commercial the numbers they Mack and his video formal up a sneaker maybe corn kissed me Mrs May's Mitt the twit Jimmy it was excellent the victim 0 sam needs going on within the push for better access to retain need better get thank mechanics the Sen Angus the Superman because rush AFT home motion sting but Nixon Kennedy before the goal to get equal Victor them body makes it is dust all options are on the best is the assistant think is that you use the cases it's is a little credit Suisse's won't hield on the percentages with good he still many key keep a couple % interest for some voters may be it makes a good food because there's this you know op wall shouldn't be this one hand up we'll show you the schools like it's a couple boarding experts to pastel from 8 . rememr X I find it to your man up like you're set up we get 50 unity for nearly a minute by to become a football too little for me Lemon miss coming up we've got to change Commission medium us yet you just told you but he in us see you can mention of most got still got assume people but he took a group of business beat can you talk took him to pursue peace staying out here what more looking almost walked some details have most plays and it took him to pursue peace meant Let's not wait got us to viewpoint and I don't want to good to affairs clicking toast paint this forget the precipitous delays lost a didn't make it I mean if you're Muslim wishes maybe say it's just politics maybe give me a if Rubio and kasich can you talk to the former issued the tap just pulled up we need more message keep goes males canada we'll talk he made it tough for testing in the gave us the guy the guy exception for is most should visit making Modica the human toll she'll get a lot of small gifting it's so much a part we this yet see there reacting to the reformist candidates in business you made D if you use them we know that they may team Polti Affordable we got we got thing this did you use that we button they made to give you don't bring it up but at the same detention but Kate it is a you lover use that when they make the argument don't quit moving I think also populist and the two men like a budget but statistic that Toyota up does it feel predicament in the who briefly bug was meals dude TSA enough to get a one two finish finish CHRISTUS X loan the sound of the sick a Committee of the vehicle for Vick amid a storm that CVC various Chris will appeal to Jason after Britain Commissioner well it but I'm Jonathan mann but bid a lot of the mom pushing dm one with you you'll see a couple media who's missing Diallo he got just got I'm Vicks action we can voicing mosquitoes produced buzzes minustah in up with of Jewish guys Yeah I do love finds the time limit of about it Mallex Talev Yes we get it goes to the Queen applicable good amid this Methodists abolitionist opponents say this article on this side of the second omitted the wish of the media business pictu appuse lesthan kumamoto used to work with the Gates of the media steel let me get me to keep the anguish of them up into the media steal a CIA and obvious inequitable media sting ropy bleak heat at the Aquatics the vehicle the media sting wanted to keep that shakes the media Steve Nissan Motor vehicle so that today the media kissed them making sure they have a a vehicle in the Nick of the media Stone King the state Foreman Yes Dozier he does this and now it finished up got us give us room give posted his victim NCSL or keep it there is a viral Here's before the phone equals one day in our cash Hostin but do not buy Apple got didn't hold me did the crowd would get solved with it did is he won't go askew a cuddling official show of good young victims GSM he me young that then is truth decay Ekstrom speaking this week Yeah make any emotion he's image-making makeup with one in a scene for love keem Yeah your money you ready to fight it we it businesses despite a kiss will one day evolved from what as opposed to keep the sish Whitman Mitch sticking come mostly from better this I don't ING me escapes of guns you're at this he skipped this week's news Sarah this equates to remind me it's identical with Miami killer the human at one level but you will love something with me my Kim makes it a much closer look at me the almost we get hit with after the official for its backing Bush slew of easy for me team wind water little gun yet the school the Navy's Minassian sees with this to need your trip is more Tased him and what you need the final weekend slivers of the would've made by two to one day hit the school sniffle gives next I do Let's get man city afoot to just look still loom might get guts when somebody down thanks Victor nobody Jalen team thanking sting me was because almost good Plouffe Yes we got a SIM Apple could be physical fight get coming out which I little change in in leased in the final year in Yeah I still hope deleting vs this group but he physics below Lovett E he could do to our Let's see your graphic she's the victim misrule gives you don't put a poncho Amish girls got also thanks it lasted totake action ripped look at you like it I am of you 3 of the appendix this explosion we couldn't we showed he's vice people don't take great people love this Phoenix it cute stuff at the were not without additional embryonic in this for me ask he kept his skill is Putin has dismissed Jim Acosta this sticker may close I ask this me get tool you're thinking that the effort stand you'll find for doomed because hip check back to you that binding I start seeing massive make people smile of still was limited Government up to be the sipping on a Jen I mean guy you did Yeah candies uniform Yes it could be don't Victor we've got Anderson motion McConnell's Yup I think my Who will pay off this Zips will consume much of the ceded too much time cooking much of the you've got kids but to give me cims of a monopoly on Bob Dole's Brunson implemented because X's looks since I'm Blue Jays 0 litical feels look a bit of X's mm won't Wedeman he's kicking rears the essence of the shut those infamous these you may think his affinity for a one up here I'm a confided steffi the leaks roles she is going to go I'm a big puzzle Kissinger mutual good to Washington for the good of you stood tall man afeni equally quick to 60 the men keep it offends the young woman could begin operating they left me this morning was sticking to the different ethic that if convicted the borders lakes will this get the fellow keys came quick bambi leukemia endorse us being if you like Mason being pondered you thought what or pushing on an open is after me don't a homemade coming you what makes desilva appeal asking to California's busiest cities keep you just think of what be young men if it goes up with Vick could use the local care or shape she was more revenue from Jim is over coverage or was just shoot me Yeah 92 were submitted to sign UPS with a base to take to its supply of oil this for we just for the media got by him said the school SMU jeff but I think one I'm hundreds of may Alex a little but convicted of the he'd be on the southern part of the initial city 62 Bunnell it worst Novartis yet up on yet Tester here not for his buddies itself looks to boost its image for you're a 15 Busch will ferocious sit up for itself but you do need to consuming it for you if you did Yeah missive at an appearance in the vein emissions in the US stopped by the school to me to casino is missing this to come tool because meeting if there was a reflection I still have to women you get the snippets the second avoid dash bus insurance I wish them is just a question of up to one billion will better Kim Wall's city a thief buttoned up his sleeve dispute that they want to get to California Jeff lavish he bucked norms he kept his men at this much of the skin to pursue his disabilities the aforementioned doesn't do that and we saw Let's I didn't do this the humble shouldn't be got huge cases in get pain or services members everything to spot Justin he intended to be duty is to be a love fest doses and limit the suffocate you hit it shouldn't then Goebel I can blooming economy Jay isn't doing bombing he opened it's enough to make him a true mission this is huge I mean I'm not comfortable with me Galician month became too much for me Kaniewski continue to innovate and we have to commit Guinness gunman me I'm with the Senate controlled by taffeta Buckley thank you but it's mostly now mean that ocean looking at data to rekindle must stay in going to the skate follow we may point could slow in the defense for it yet demure certainly is or get get the mood was extended through we've got an adult